PERSEPSI MASYARAKAT TERHADAP PENGELOLAAN AGROSILVOPASTURA DI HUTAN RAKYAT DESA KARYASARI - Baihaqi, Wahyu Indra; Supriono, Bambang; meiganati, kustin bintani (Jurnal Nusa Sylva, 2022)
Forest management by the people independently has been promoted by the government since the 1980s. As a result, people are now starting to understand the importance of forest management on privately owned land. The function of private forests, apart from increasing people's income, is also for soil and water conservation. The impact of the function of soil and water conservation is widely felt by the community, not only by land owners. The community's sustainable forest management model is managed by combining timber plants with agricultural crops, to obtain benefits more quickly. This method is better known as agroforestry. Agroforestry management develops by combining three commodities, namely timber, agricultural crops and livestock crops, which is called agrosilvopastura. The management of agrosilvopastura is still not widely known by the community, therefore in this stud, we want to know the level of public understanding or perception of the community about the management of agorsilvopastura. The research was conducted in Karyasari Village, Leuwiliang District, Bogor Regency. It was carried out in Leuwiliang District because the potential for community forest is quite large for the Bogor Regency area. Methods of data collection by distributing closed questionnaires and processing with a Likert scale. The results of this study indicate that the people of Karyasari Village have a good perception of 4.328 on the Likert scale. This shows that the people of Karyasari Village have a good understanding of the implementation of agrosilvopastura. Agrosilvopastura activities in Karyasari Village have been well integrated so that they can provide a high contribution to community income, namely 53% from the forestry sector, 24.8% from the agricultural sector and 9.1% from the livestock sector.